MicroRNA-143 Regulates Human Osteosarcoma Metastasis by Regulating Matrix Metalloprotease-13 Expression - Osaki, Mitsuhiko (Nature Publishing Group, 2011)
Pulmonary metastases are the main cause of death in patients with osteosarcoma, however, the molecular mechanisms of metastasis are not well understood. To detect lung metastasis-related microRNA (miRNA) in human osteosarcoma, we compared parental (HOS) and its subclone (143B) human osteosarcoma cell lines showing lung metastasis in a mouse model. miR-143 was the most downregulated miRNA (P < 0.01), and transfection of miR-143 into 143B significantly decreased its invasiveness, but not cell proliferation. Noninvasive optical imaging technologies revealed that intravenous injection of miR-143, but not negative control miRNA, significantly suppressed lung metastasis of 143B (P < 0.01). To search for miR-143 target mRNA in 143B, microarray analyses were performed using an independent RNA pool extracted by two different comprehensive miR-143-target mRNA collecting systems. Western blot analyses revealed that MMP-13 was mostly protein downregulated by miR-143. Immunohistochemistry using clinical samples clearly revealed MMP-13-positive cells in lung metastasis-positive cases, but not in at least three cases showing higher miR-143 expression in the no metastasis group. Taken together, these data indicated that the downregulation of miR-143 correlates with the lung metastasis of human osteosarcoma cells by promoting cellular invasion, probably via MMP-13 upregulation, suggesting that miRNA could be used to develop new molecular targets for osteosarcoma metastasis.